The influence of Manto and Maupassant on social life - Aqeela Shaheen; Riaz Qadeer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Literature is expression and interpretation of life. The Realism of life is exhibited in the literary masterpieces of the writers who understand life and possess enough courage to express it in their creative writings. This is quite befitting for French writer Guy De Maupassant and Urdu writer Saadat Hassan Manto. They, through their world famous short stories, put a great impact on world literature. Their special field is Realism. They painted life as it appeared to them. They were blamed for vulgarity and resultantly suffered for that matter. The researchers and critics have acknowledged their love for humanity and their superiority as writers and as trend setters.
Keywords: 330